2021
DOI: 10.2147/jpr.s309693
|View full text |Cite
|
Sign up to set email alerts
|

Full-Endoscopic Lumbar Decompression versus Open Decompression and Fusion Surgery for the Lumbar Spinal Stenosis: A 3-Year Follow-Up Study

Abstract: Compare the efficacy of full-endoscopic lumbar decompression surgery (FELDS) and open decompression and fusion surgery (ODFS) for lumbar spinal stenosis (LSS). Patients and Methods: A retrospective analysis of 358 LSS patients treated by FELDS ("FELD" group) or ODFS ("open" group) was undertaken. There were 177 patients in the FELDS group with a mean age of 65.47±9.26 years and 181 patients in the open group with a mean age of 64.18±10.24 years. Duration of follow-up was 38.63±11.88 months in the FELDS group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…PETD can not only remove disc herniation but also hyperplastic facet joints, hypertrophic ligamentum flavum, and osteophytes, which can increase the scale of the foramen, lateral recess, and even the central canal. According to a few studies, PETD showed clinical outcomes comparable to the conventional open decompression and fusion surgery, with advantages of lesser tissue trauma, faster rehabilitation, and lower intraoperative blood loss, risk of degeneration of adjacent segments and cost of postoperative care [ 8 10 ]. However, surgery-related complications have become more common and inevitable because of the widespread use of PETD, which makes patients dissatisfied with the postoperative efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…PETD can not only remove disc herniation but also hyperplastic facet joints, hypertrophic ligamentum flavum, and osteophytes, which can increase the scale of the foramen, lateral recess, and even the central canal. According to a few studies, PETD showed clinical outcomes comparable to the conventional open decompression and fusion surgery, with advantages of lesser tissue trauma, faster rehabilitation, and lower intraoperative blood loss, risk of degeneration of adjacent segments and cost of postoperative care [ 8 10 ]. However, surgery-related complications have become more common and inevitable because of the widespread use of PETD, which makes patients dissatisfied with the postoperative efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relative conservative approach and lower complication rate, it is a preferred surgical option for the elderly (9).However, traditional laminectomy decompression surgery may lead to damage to the posterior lumbar muscle structure, particularly the multi dus muscle. The subsequent loss of innervation and fat in ltration may be associated with chronic lower back pain and failed back surgery syndrome (10). As a result, there has been a shift in focus towards minimally invasive surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Within natural aging and lumbar spine degeneration, lumbar degenerative disease is characterized by hypertrophy of facet joint and ligamentum flavum, degeneration of intervertebral disc, collapse of intervertebral space, and osteophyte formation 1 , 2 . This disease can cause pain and disability, place a heavy burden on the health care system, and restrict economic development.…”
Section: Introductionmentioning
confidence: 99%